(untitled) (Research, Society and Development, 2021)
The cultivation of cover crops under no-tillage systems can promote positive improvements in soil attributes and promote increases in grain yield of successor crops, such as soybeans. The aim of this work was to evaluate the evolution of soil cover and accumulation of dry shoot phytomass of autumn/winter cover crops and their impact on the agronomic performance of soybean grown in succession. Black oats (Avena strigosa), rye (Secale cereale) and turnip (Raphanus sativus) were used as cover species in single crops, dual and triple intercropping, in addition to the fallow and weeded controls. The percentage of soil cover (%) and the accumulation of dry shoot phytomass were evaluated at 30, 45, 60, 75, 90 and 105 days after sowing (DAS). In soybean crop, plant height, number of productive nodes per plant, number of pods per plant, mass of a thousand grains and grain yield were evaluated. The cultivation of turnip single provided the fastest soil coverage, with 90.0% at 45 DAS. The intercropping between rye + turnip provided the largest accumulations of dry shoot phytomass, greater than 7.0 Mg ha-1 at 105 DAS. The highest soybean yields were obtained in succession to the cultivation of black oat and rye in single, yielding approximately 3,300 kg ha-1, 50% higher compared to fallow and weeded treatments.